Pyloromyotomy in a patient with paramyotonia congenita - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2004)
A 2-mo-old infant with paramyotonia. congenita was scheduled for pyloromyotomy and repair of inguinal hernia. Diagnosis of paramyotonia congenita was done with positive family history, myotonia at eyelids, provocation by cold, and electromyogram analysis. Anesthesia was induced via face mask with sevoflurane at 4 minimum alveolar anesthetic:concentration in oxygen. Tracheal intubation was attempted without a neuromuscular relaxant. Anesthesia was maintained with sevoflurane at 0.5 minimum alveolar anesthetic concentration in oxygen and remifentanil infusion at a rate of 0.2 mug (.) kg(-1 .) min(-1). After discontinuation of sevoflurane and remifentanil, the patient was awake and had full recovery of muscle activity.
Keywords: PROPOFOL; PARALYSIS